Análisis comparativo de Frameworks para el desarrollo de aplicaciones móvil. - Muñoz Barriga, Leonela Julissa (2024)
In this case study, a comparative analysis of the Frameworks used for mobile application development was conducted, leading to the identification of the most commonly used Frameworks that provide programmers with the key features enabling them to perform specific tasks, namely cost, flexibility, and investment of time and energy. During the research, the questions and objects of the investigation were determined, followed by the establishment of the objectives and basic concepts of the research method. Bibliographic research was employed, including real information, reports, and articles. Additionally, a comparative study was conducted, which involved developing features for each selected framework in written form. Specifically, the study examined their reliability, usability, or effectiveness to provide developers with information indicating which type of framework is recommended, valid, or most suitable for the type of mobile application they plan to create.